Self-Help Groups: Importance of Credit and Training in creating opportunity to the members in Kanpur Dehat - Ruchika; kapoor, Shivani kapoor (International Journal of Psychosocial Rehabilitation, 2020)
The Self-Help Groups (SHGs) are voluntary associations of people formed to attain some common goals. These are groups that have similar social identity, heritage, caste or traditional occupations and come together for a common cause and manage resources for the benefit of the group members. In this paper, it is seen that how credit and skill can provide opportunity to the members of SHGs. Credit access is one of the major benefit to the members of SHGs which can be more useful if proper skill training for employability provided to them.